(x-\(\frac{1}{2}\)).1+5x=0
\(\frac{37-x}{x+13}\)\(=\)\(\frac{3}{7}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, vì m vuông góc AB
n vuông góc AB
=> m //n
b do m//n
=> góc C= 90
\(\left(\frac{3}{4}\right)^{2.x}:\left(\frac{2}{5}\right)^{10}=\left(\frac{15}{8}\right)^{10}\)
\(\left(\frac{3}{4}\right)^{2.x}=\left(\frac{15}{8}\right)^{10}.\left(\frac{2}{5}\right)^{10}\)
\(\left(\frac{3}{4}\right)^{2.x}=\left(\frac{15}{8}.\frac{2}{5}\right)^{10}\)
\(\left(\frac{3}{4}\right)^{2.x}=\left(\frac{3}{4}\right)^{10}\)
\(\Rightarrow2.x=10\Rightarrow x=5\)
\(\left(\frac{3}{4}\right)^{2x}\div\left(\frac{2}{5}\right)^{10}=\left(\frac{15}{8}\right)^{10}\)
\(\left(\frac{3}{4}\right)^{2x}=\left(\frac{15}{8}\right)^{10}\times\left(\frac{2}{5}\right)^{10}\)
\(\left(\frac{3}{4}\right)^{2x}=\left(\frac{15}{8}\times\frac{2}{5}\right)^{10}\)
\(\left(\frac{3}{4}\right)^{2x}=\left(\frac{3}{4}\right)^{10}\)
\(\Rightarrow\)\(2x=10\)
\(\Rightarrow\)\(x=5\)
\(\left(x-\frac{1}{2}\right).1+5x=0\)
\(\Rightarrow x-\frac{1}{2}+5x=0\)
\(\Rightarrow x+5x=\frac{1}{2}\)
\(\Rightarrow6x=\frac{1}{2}\)
\(\Rightarrow x=\frac{1}{12}\)
\(\frac{37-x}{x+13}=\frac{3}{7}\)
=> 3 . ( x + 13 ) = 7 . ( 37 - x )
=> 3x + 39 = 259 - 7x
=> 10x = 220
=> x = 22